Testing the effectiveness of Pasu Sakhi: An innovation for resource poor farm women in Rajasthan - PONNUSAMY, K; CHAUHAN, A K; MEENA, SUNITA (The Indian Journal of Animal Sciences, 2017)
The present investigation was conducted to assess the effectiveness of Pasu Sakhi, a woman empowerment model in animal husbandry which is being carried out through Mahila Kisan Sashaktikaran Pariyojana (MKSP), a sub-component of National Rural Livelihood Mission (NRLM). The study was conducted in four districts of Rajasthan namely Alwar, Dholpur, Tonk and Dausa where the livestock component is being implemented through Pasu Sakhi (PS) model. The data were collected in the month of April 2016 by focused group discussions, observation and a semi-structured interview schedule to elicit the response from PS and woman farmer clients. The results revealed that the Project Implementing Agency (PIA) in Rajasthan, namely Centre for micro Finance (CmF), Jaipur effectively harnessed the social capital which was built up over a decade in earlier projects and greatly helped to achieve the targets set aside at grass root level through partner organisations in each selected district. The beneficiaries, although belonged to poor households could able to adopt few selected technologies such as deworming, mineral mixture feeding and milk products preparation. This paper discusses the various parameters of effectiveness of Pasu Sakhi model and suggests measures to further strengthen the same as a future demand driven gender sensitive decentralised extension model in the animal husbandry sector.